Secular Trends in Birth Weight in Chile and Its Regions Between 1990 and 2021 - Morales-Campos, D (John Wiley and Sons Inc, 2025)
Objective: The objective is to analyze secular trends in birth weight (BW) for Chile from 1990 to 2021, focusing on the mean BW and low birth weight (LBW) prevalence, and to assess differences across Chilean regions. Methods: Our sample, obtained from the Chilean National Statistics Office, contains information on 7 822 975 births, including the total births that took place in Chile from 1990 to 2021. We calculated mean BW and LBW prevalence at a national and a regional level. We also gathered national aggregates from 1974 to 1989 from secondary sources. Results: At a national level, mean BW increased sharply in Chile from 1983 to 1994 (6%), remained stagnant thereafter, and fell slightly during the last decade and a half. LBW prevalence declined substantially from the mid-1970s to the mid-1990s, from 12% to 5%. It stagnated during the early 1990s, after which there was a small but continuous increase to over 6.5%. Antofagasta is the only outlier: its mean BW and the percentage of LBW are permanently lower and higher, respectively. Conclusions: A sharp increase in mean BW from the mid-1980s to the mid-1990s, together with the declining percentage of LBW from the mid-1970s to the mid-1990s, should be due to the better nutritional status of mothers. The decline in mean BW from the early 2000s (as well as the increasing percentage of LBW) may be due to an increasing proportion of preterm births and the increase in the age of women giving birth. The relatively poor performance of Antofagasta is explained by the region s high altitude, which affected large numbers of the population. © 2025 Wiley Periodicals LLC.